Migraine Headache Day Response Rates and the Implications to Patient Functioning: An Evaluation of 3 Randomized Phase 3 Clinical Trials of Galcanezumab in Patients With Migraine. Issue 10 (29th November 2020) - Ford, Janet H.; Kurth, Tobias; Starling, Amaal J.; Ayer, David W.; Wietecha, Linda A.; Port, Martha D.; Rettiganti, Mallikarjuna; Ruff, Dustin D.
Abstract : Objective: This post hoc study investigated the relationship between patient response in terms of migraine headache day reduction and patient‐reported outcomes of health‐related quality of life (HRQoL) and disability categories. Background: Migraine causes considerable disease‐related disability and negatively impacts HRQoL of patients. Calcitonin gene‐related peptide inhibitors improve these outcomes and may eliminate disability due to migraine in some patients. Methods: Analyses used data from 3 double‐blind, placebo (PBO)‐controlled, phase 3 studies in adults with episodic migraine (EM) (EVOLVE‐1: N = 858 and EVOLVE‐2: N = 915) or chronic migraine (CM) (REGAIN: N = 1113). Patients were randomized 2:1:1 to subcutaneous injection of PBO, galcanezumab (GMB) 120 mg, or GMB 240 mg once monthly for 6 months in EVOLVE‐1 and ‐2 and for 3 months in REGAIN. Primary endpoint was overall mean change from baseline in monthly migraine headache days. Patients were divided into 4 response‐level groups based on percent change from baseline (<30%, ≥30% to <50%, ≥50% to <75%, ≥75%). Patient‐reported outcomes included the 14‐item Migraine‐Specific Quality of Life Questionnaire version 2.1 (MSQ) and Migraine Disability Assessment (MIDAS) questionnaire. Results: Among patients with migraine, mean improvements from baseline in MSQ domain scores increased with each successive level of migraine headache day response. On a 100‐pt scale, increases in Role Function‐Restrictive score in EM were 16.8 and 36.0 at the <30% and ≥75% response levels, respectively, and for CM were 10.7 and 46.5. Similar patterns in scores were observed for the Role Function‐Preventive and Emotional Function domains. Examination of improvement in MSQ item score by treatment group showed that, in patients with EM, approximately 10 to 20% more GMB‐treated patients (N = 796 for GMB 120 mg and GMB 240 mg) had improvements in all 14 MSQ items compared with PBO‐treated patients (N = 773) (all P  < .001). In patients with CM, 3 to 16% more GMB‐treated patients (N = 507) had improvements in the 14 MSQ items compared with PBO (N = 494), though differences were statistically significant in only 19 of 28 comparisons. At baseline, mean MIDAS scores (EM, 33.1; CM, 67.2) indicated severe mean disability for patients with EM and very severe disability for patients with CM. Among patients with EM, 215 of 425 (50.6%) of those treated with GMB 120 mg and 212 of 413 (51.3%) treated with 240 mg had little/no disability due to migraine after 6 months (PBO: 277 of 832 (33.3%), P  < .001 for both). Among patients with CM, 50 of 254 (19.7%) of those treated with GMB 120 mg and 54 of 258 (20.9%) treated with 240 mg reached the level of little/no disability after 3 months of treatment (PBO: 70 of 504 (13.9%), P  = .045 for 120 mg, P  = .017 for 240 mg). Conclusions: Because migraine greatly impairs an individual's ability to participate in activities of daily living, measurements of HRQoL are essential in clinical research. This study showed that function in daily life, as measured by MSQ score, improved as migraine headache days were reduced and that GMB‐treated patients were more likely to see improvement in MSQ item scores compared with PBO‐treated patients. Elimination of migraine‐related disability was also more frequent in GMB‐treated patients compared with placebo‐treated patients.